A BUDDHIST VIEW OF ECOLOGY: INTERDEPENDENCE, EMPTINESS AND COMPASSION - Pensa, Corrado (Journal of Dharma, 2001)
Interdependence, emptiness and compassion represent three very significant themes in the Buddhist teachings. Although they are especially developed in certain Mahayana and Vajrayana schools, we can safely say that interdependence, emptiness and compassion are integral and important elements of Buddhist doctrine, beginning from the very teachings directly attributed to the Buddha down to the later schoðls we just mentioned. And the impact of these three basic ingredients of Buddhism is obviously all-pervasive both in terms of Buddhist doctrine as well as in terms of Buddhist meditation practices.